An Overview of Islamic Law on Accommodation Leasing in Nglanjaran, Sardonoharjo Village, Ngaglik Sub District, Sleman Regency - M. Roem Syibly; Dani Arisman (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2019)
This study focuses on the contract implementation to lease an accommodation according to Islamic law. This study aims to explain the practices in accommodation leasing in Nglanjaran, Sardonoharjo Village, Ngaglik District, Sleman Regency, Yogyakarta and to examine the accommodation leasing practices based on Islamic law. This research used a field research method, with a descriptive analytical approach. The data were collected through observation and interviews. This research shows that the agreement made between the tenant and the accommodation owner was done orally and in writing. This was done in accordance with Islamic law as it fulfills the essential principles and requirements of ijarah. The prices and the period of lease has been determined based on various facilities provided such as physical and non-physical facilities. Meanwhile, disputes that may occur in leasing practices are settled through a negotiation for consensus. To avoid agreement violation, the requirements or any issue related to the lease agreement shall be clearly written to avoid any ambiguity and misunderstanding in the future. In addition, it is suggested that the village apparatus be involved in the arrangement of the lease practice, by way of making general regulations for accommodation leasing in Nglanjaran for community comfort.